T-CAST: An optimized CAST-Seq pipeline for TALEN confirms superior safety and efficacy of obligate-heterodimeric scaffolds - Rhiel, Manuel; Geiger, Kerstin; Andrieux, Geoffroy; Rositzka, Julia; Boerries, Melanie; Cathomen, Toni; Cornu, Tatjana I. (Frontiers in Genome Editing, 2023)
Transcription activator-like effector nucleases (TALENs) are programmable nucleases that have entered the clinical stage. Each subunit of the dimer consists of a DNA-binding domain composed of an array of TALE repeats fused to the catalytically active portion of the FokI endonuclease. Upon DNA-binding of both TALEN arms in close proximity, the FokI domains dimerize and induce a staggered-end DNA double strand break. In this present study, we describe the implementation and validation of TALEN-specific CAST-Seq (T-CAST), a pipeline based on CAST-Seq that identifies TALEN-mediated off-target effects, nominates off-target sites with high fidelity, and predicts the TALEN pairing conformation leading to off-target cleavage. We validated T-CAST by assessing off-target effects of two promiscuous TALENs designed to target the CCR5 and TRAC loci. Expression of these TALENs caused high levels of translocations between the target sites and various off-target sites in primary T cells. Introduction of amino acid substitutions to the FokI domains, which render TALENs obligate-heterodimeric (OH-TALEN), mitigated the aforementioned off-target effects without loss of on-target activity. Our findings highlight the significance of T-CAST to assess off-target effects of TALEN designer nucleases and to evaluate mitigation strategies, and advocate the use of obligate-heterodimeric TALEN scaffolds for therapeutic genome editing.